Integrated Retail Observability Architecture: From Data Sources to Executive Insights - Bhatia, Rahul (International Journal of Computing and Engineering, 2025)
The retail industry has undergone a transformative shift from traditional inventory management to sophisticated data-driven operations, necessitating advanced observability platforms to maintain a competitive advantage. This article explores how modern observability solutions, particularly platforms like Splunk, revolutionize retail operations through enhanced inventory accuracy and fraud detection capabilities. The article explores the conceptual foundations of observability architectures, encompassing the data acquisition, transformation, and presentation tiers that convert unprocessed operational information into strategic business insights. Through analysis of Radio Frequency Identification (RFID) technology integration, cross-system correlation mechanisms, and advanced pattern recognition algorithms, the article demonstrates how retailers achieve unprecedented visibility into their operations. The article reveals how observability platforms enable real-time monitoring of diverse data streams from Point of Sale (POS) systems, network traffic, and inventory management systems, creating unified views that detect anomalies and prevent fraud through multi-vector analysis strategies. Implementation strategies emphasizing data standardization, executive dashboard design, and return on investment considerations provide practical guidance for retail organizations. The article concludes by exploring emerging trends in artificial intelligence and machine learning integration, showcasing how next-generation observability platforms will continue to transform retail operations through predictive analytics and prescriptive recommendations.